Reframing mass participation events as active leisure: Implications for tourism and leisure research. (July 2021) - Hillman, Peita; Lamont, Matthew; Scherrer, Pascal; Kennelly, Millicent
Abstract: This paper proposes the term 'active leisure events' to ameliorate fragmentation of research concerned with 'mass-participation' events primarily aimed at non-elite participants. This literature is characterised by semantically diverse terminology despite such events sharing a range of unifying characteristics centring around an ethos of being open to all; fundamentally encouraging participation in physical activity; embodied, self-propelled mobility; use of re-ordered space; and providing a meeting place for nuanced social worlds. Despite their commonalities, active leisure events may also exhibit considerable inter-event variability. This paper presents an integrative review of existing literature, augmented by practice examples, to support more coherent theoretical and applied research efforts in this space. Based on this integrative review, the 'active leisure events framework' is proposed as a conceptual reference point to facilitate coherent and informed discourse, allowing tourism and leisure researchers and practitioners to clearly identify key characteristics of the events they engage with. Highlights: Provides a critical synthesis of mass-participation event research and terminology. Challenges the traditional conceptual lens of sport and argues for active leisure as a more appropriate and unifying concept. . Identifies and outlines the unifying and variable characteristics of active leisure events. Presents the active leisure events framework to facilitate improved transparency and strengthen future discourse within tourism and leisure research contexts.